Proto Language: Discussions of Origin - Butt, Faiza (sourcecoder, 2024)
Search for the existence and the origin of "Proto Language" or the "Mother Language of all the languages” on earth has arose a lot of speculations by linguists and scholars, who led to a number of lingual researches regarding above mentioned phenomenon. Numerous religious based, mythological and philosophical ideologies occur proving, somehow, the origin and existence of "Proto Language". This article sums up all that discussions.